Tingkat Kesabaran Santri dalam Melaksanakan Kegiatan Sehari-Hari di Pondok Pesantren Al-Muhajirin Purwakarta - Widy Khoerurotussaadah; Yumna Yumna; Tamami Tamami (Jurnal Riset Agama, 2022)
At the Al-Muhajirin Islamic Boarding School there are SMA and MA students where the difference between the two is high school students who do not study Sufism and MA students who study Sufism, therefore both of them must have different levels of patience even though their positions are the same students. Therefore, the purpose of this study was to find out how the level of patience between high school and MA students at the Al-Muhajirin Islamic Boarding School was. This study uses qualitative research methods with observation and interview techniques. The results and discussion of the research are in carrying out daily activities at this Islamic Boarding School, the importance of patience in each student to be able to face the destiny that God has determined, face God's favors and face all the trials that God has given. The conclusion in this study shows that in carrying out their daily activities at Islamic boarding schools, there are differences in the level of patience between high school and MA students. Where high school students are at the iffah level and MA students are at qana'ah. It is hoped that further research can use different research methods in order to obtain more comprehensive results.